An Aggressive Form of Langerhan Cell Histiocytosis in an Adult: Therapeutic Challenges - Karan Seegobin; Satish Maharaj; Cherisse Baldeo; Amal Shukri; Fauzia N. Rana (Case Reports in Oncological Medicine)
Langerhans cell histiocytosis (LCH) is rare in adults. Regular follow-up is mandatory due to reoccurrence. A 35-year-old male with an incidental left iliac bone lesion was diagnosed with LCH. He later became symptomatic with hip pain and spread of the disease. Despite excision of the symptomatic iliac lesion, he had progression while on cytarabine and nivolumab, evidenced by increased bone pain and involvement of other bones on imaging. He underwent excision of the jaw lesion followed by vinblastine; he was pain free and had stable disease on PET imaging after 3 months. LCH is an uncommon neoplasia. Treatment is reserved for symptomatic patients while asymptomatic patients are observed. Follow-up is imperative due to the risk of reoccurrence. Despite surgical treatment together with one of the front-line agents for refractory disease, in this case cytarabine, he still had progression of the disease. Furthermore, the trial of nivolumab was of no benefit. This case highlights good response to vinblastine which is previously reported to have good success. No trials are published, and the optimal strategy has yet to be defined. LCH with multiple bony involvement can be aggressive and therapeutically challenging.